Choroid plexus asymmetry predicts decline in fundus blood flow in white matter hyperintensity patients: insights from SS-OCTA - Zeqi Shen; Weitao Yu; Jiawei Ye; Shouxuan Gao; Jie Zheng; Liang Yu; Faliang Gao; Chaoyang Hong; Sheng Zhang (Therapeutic Advances in Ophthalmology)
Background: This study aims to identify ocular fundus blood flow biomarkers, using swept-source optical coherence tomography angiography (SS-OCTA), that reflect choroid plexus (CP) changes in patients with white matter hyperintensities (WMHs). Design: This is a retrospective analysis based on prospective data. Methods: The study was an analysis of collected data from patients with WHMs who underwent multimodal magnetic resonance imaging (MRI) and SS-OCTA (FRESH-CSVD study, NCT06431711). Automatic segmentation was used to calculate the volumes of CP and WMHs. The bilateral CP asymmetry index was defined as the value of the difference in volume between the right and left CP, divided by the volume of the left CP. The association between SS-OCTA parameters, CP volume and its asymmetry index, and WMH volume (WMH-V) was analyzed using a LASSO-derived logistic regression model, with mediation analysis to explore their connections. Results: The study included 240 eyes from 137 patients. A significant correlation was found between the bilateral CP asymmetry index and WMH-V (β = −6.03, 95% CI: −11.36 to −0.70, p  = 0.027). WMH-V was correlated with the optic nerve head choriocapillaris perfusion area (ONH CC PA) (β = −2.95, 95% CI: −5.62 to −0.28, p  = 0.031). The bilateral CP asymmetry index was also related to ONH CC PA (β = 0.07, 95% CI: 0.01 to 0.13, p  = 0.027). Mediation analysis showed that WMH-V mediated 15.11% of the association between the bilateral CP asymmetry index and ONH CC PA ( p  = 0.036), but this mediation effect disappeared after adjusting for age. Conclusion: These findings suggest that the morphological changes of the CP have a significant impact on the ONH blood flow in patients with WMHs. The ONH CC PA shows potential as a biomarker for detecting morphological changes of CP among WMHs patients.